Minoxidil delivered via a stem cell membrane delivery controlled release system promotes hair growth in C57BL/6J mice - Song, Dandan; Pan, Shouxi; Jin, Wenxia; Wu, Ronghui; Zhao, Tianqi; Jiang, Jinlan; Zhu, Mingji (Frontiers in Bioengineering and Biotechnology, 2024)
Umbilical cord-derived mesenchymal stem cell membrane-loaded minoxidil (MXD) nanoparticles (STCM-MXD-NPs) were prepared to investigate their effects on hair growth in C57BL/6J mice.STCM-MXD-NPs were obtained by freeze-thawing and differential centrifugation, and their effects on hair growth were evaluated using C57BL/6J mice. The mRNA and protein expression levels of vascular endothelial growth factor (VEGF) and insulin-like growth factor-1 (IGF-1) were detected by real-time polymerase chain reaction and enzyme-linked immunosorbent assays, respectively. Protein expression levels of marker of proliferation Ki-67 (MKI67) and β-catenin (CTNNB) in skin tissue were detected by immunohistochemistry.STCM-MXD-NPs improved MXD solubility. They released the drug slowly, increasing its transdermal properties, accumulation in the skin, and content in the hair bulb tissues with a better efficacy than that of ordinary MXD. Moreover, STCM-MXD-NPs significantly upregulated the mRNA and protein levels of VEGF and IGF-1 and promoted the protein expression of MKI67 and CTNNB in mouse skin tissues, promoting mouse hair growth.Stem cell membrane-loaded MXD nanoparticles with slow-release properties increased MXD accumulation in the skin by improving its transdermal properties, increasing VEGF, IGF-1, MKI67, and CTNNB expression levels and promoting hair growth in C57BL/6J mice.